1997
DOI: 10.1006/dbio.1997.8619
|View full text |Cite
|
Sign up to set email alerts
|

Both Myoblast Lineage and Innervation Determine Fiber Type and Are Required for Expression of the Slow Myosin Heavy Chain 2 Gene

Abstract: Skeletal muscle fibers express members of the myosin heavy chain (MyHC) gene family in a fiber-type-specific manner. In avian skeletal muscle it is the expression of the slow MyHC isoforms that most clearly distinguishes slow- from fast-contracting fiber types. Two hypotheses have been proposed to explain fiber-type-specific expression of distinct MyHC genes during development-an intrinsic mechanism based on the formation of different myogenic lineage(s) and an extrinsic, innervation-dependent mechanism. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 56 publications
8
65
0
Order By: Relevance
“…This has been previously suggested by the studies of the expression patterns of muscle sarcomeric genes during regeneration in the presence or the absence of nerve (45) or after muscle stimulation (43,44). Recently, it has been shown that in chicken myotubes, the expression of the myosin heavy chain 2 slow gene depends on both intrinsic (type of myoblasts) and extrinsic (nerve-induced contraction) factors (46). The present study shows that the precise regulation of pM results from the combination of different transcriptional regulatory elements associated with these different programs whose relative contribution may evolve during muscle maturation.…”
Section: Fig 6 Pm310cat Transgenes Activity Is Altered In Adr Micementioning
confidence: 76%
“…This has been previously suggested by the studies of the expression patterns of muscle sarcomeric genes during regeneration in the presence or the absence of nerve (45) or after muscle stimulation (43,44). Recently, it has been shown that in chicken myotubes, the expression of the myosin heavy chain 2 slow gene depends on both intrinsic (type of myoblasts) and extrinsic (nerve-induced contraction) factors (46). The present study shows that the precise regulation of pM results from the combination of different transcriptional regulatory elements associated with these different programs whose relative contribution may evolve during muscle maturation.…”
Section: Fig 6 Pm310cat Transgenes Activity Is Altered In Adr Micementioning
confidence: 76%
“…Because differentiation of fiber types in fetal skeletal muscle appears to be regulated by both the intrinsic genetic programs within myoblasts and the extrinsic local environment (DiMario and Stockdale, 1997;Robson and Hughes, 1999;Pin et al, 2002), we want to determine whether Sox6 is involved in intrinsic myogenic commitment or/and in regulating the extrinsic signals. To begin to answer this question, we have obtained Sox6 conditional knockout mice (Dumitriu et al, 2006a) to inactivate the Sox6 gene in a myogenic cell-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…This was most evident in the curare-treated fetal MA in which secondary muscle fibers did not contain detectable levels of slow MyHC2 (DiMario and Funk, 1999). Normal innervation-dependent regulation of slow MyHC2 gene expression was observed in vitro by innervation of MA muscle fibers and subsequent slow MyHC2 gene expression (DiMario and Stockdale, 1997). Fast PM muscle fibers in vitro were resistant to innervation-induced slow MyHC2 gene expression, suggesting a muscle fiber typespecific mechanism of slow MyHC2 gene repression in these fibers.…”
Section: Introductionmentioning
confidence: 93%
“…Spinal cord explants containing motor neurons from E5 chick embryos were added to some of the cultures on day 3 of incubation as previously described (DiMario and Stockdale, 1997). On day 4 of incubation, medium for some of the cultures was supplemented with 100 µM 2-aminoethoxydiphenylborate (2-APB) (Sigma) or 10 µM xestospongin D (Calbiochem).…”
Section: Cell Culturementioning
confidence: 99%